SURVEILLANCE AND IMPLICATIONS OF WIRETAPPING IN INTERNATIONAL AND NATIONAL LAW: A COMPARATIVE STUDY OF ARRANGEMENTS AND PRACTICES - Gunawan Widjaja; Adrian Bima Putra (Jurnal Komunikasi, 2025)
This research addresses the surveillance and implications of wiretapping in the perspective of international and national law through a comparative study of regulation and practice, with a focus on the cases of Indonesia and Australia. Wiretapping is an important instrument in law enforcement and state security, but at the same time has the potential to violate human rights, particularly the right to privacy. At the international level, wiretapping is regulated through various human rights instruments such as the UDHR, ICCPR, and the Vienna Convention, which emphasise the protection of privacy and the principle of non-intervention, while leaving room for exceptions for serious crimes. At the national level, Indonesia faces challenges of regulatory fragmentation, weak oversight, and the absence of a specific law that comprehensively regulates wiretapping. The case study of Australia's wiretapping of Indonesia shows that the practice of wiretapping without adequate oversight can damage diplomatic relations and reduce trust between countries. This research recommends harmonising national regulations with international standards, establishing a comprehensive wiretapping law, and strengthening independent oversight institutions to ensure lawful, proportionate and accountable wiretapping practices, while protecting human rights and maintaining stable international relations